Complementary Effect of Processed Broiler Offal and Feather Meals on Nutrient Retention, Carcass and Organ Mass of Broiler Chickens - Isika, M.A.; Agiang, E.A.; Eneji, C.A. (International Journal of Poultry Science, 2006)
Studies were carried out to assess the complementary effect of broiler offal (BOM) and broiler hydrolyzed feather meals (HBFM) processed using simple low cost technologies on the nutrient retention, carcass characteristics and organ mass of broiler chickens. Four diets each were formulated for the starter and finisher phases. Diet A was the control while, B and C contained 30g/kg diet of BOM or HBFM each, and D had a combination of 15:15g/kg of BOM: HBFM. The formulation was at the expense of fishmeal, which was 30g/kg in the control diet. The starter and finisher diets contained 230g and 210g crude protein/kg, respectively and supplied 3000 Kcal/kg of metabolizable energy for the two phases. 180 day-old Anak 2000 broilers were randomly divided into 12 groups of 15 birds each. Each diet was fed to three groups of the chicks in a fully randomize manner. Results showed that the retention of dry matter, crude protein, crude fiber, calcium and phosphorus were not significantly (P>0.05) affected in both the starter and finisher phases. The retention of ether extract was significantly (P< 0.05) least in diet B, while birds fed on diet D had significantly (P< 0.05) the highest retention. Eviscerated mass; drumstick, thigh and breast of broilers at 49 days old were not significantly (P>0.05) affected. The abdominal fat pad was significantly (P< 0.05) least (0.67%) in the HBFM ingredient diet (C) but highest (1.33%) in BOM diet. The liver, spleen, heart, kidney and gizzard were not significantly (P>0.05) influenced by the combined effect of the by-products. It is concluded from the study that broiler offal and broiler hydrolyzed feather meals (Diet D) complemented each other as alternative feed ingredients in broiler nutrition.